THE IMPACT OF UTILIZING INTERACTIVE CONCEPTUAL INSTRUCTION ASSISTED BY PHET SIMULATIONS ON STUDENTS' UNDERSTANDING ABILITY IN PHYSICS - M Furqon (SPEKTRA: Jurnal Kajian Pendidikan Sains, 2024)
The objective of this study is to assess the effects of employing Interactive Conceptual Instruction with the assistance of PhET Simulations on students' understanding ability in the field of physics. The study employed a quasi-experimental research approach, specifically utilizing a matching-only pretest-posttest control group design. The sample consisted of 62 students from a high school in Indonesia. The utilized instrument was a understanding ability test in the modified Bloom's Taxonomy. The acquired data were subjected to analysis using t-test and N-Gain. There is a significant difference in the understanding of abilities among students who are enrolled in interactive conceptual instruction facilitated by PhET simulation compared to those who are enrolled in interactive conceptual instruction without any assistance from PhET simulation. The findings of the study indicate that the utilization of Interactive Conceptual Instruction Assisted by PhET Simulations has the potential to enhance students' understanding ability in the field of physics.